Structural characterization of a hydroperoxo nickel complex and its autoxidation: mechanism of interconversion between peroxo, superoxo, and hydroperoxo species - Rettenmeier, Christoph Alexander; Wadepohl, Hubert; Gade, Lutz H. (Angewandte Chemie, 2015)
Pincer-stabilized nickel(I) complexes readily react with molecular oxygen to form dinuclear 1,2-μ-peroxo-bridged nickel(II) complexes, which are the major components of a dynamic equilibrium with the corresponding mononuclear superoxo species. The peroxo complexes further react with hydrogen peroxide to give the corresponding nickel(II) hydroperoxides. One of these hitherto elusive species was characterized by X-ray diffraction for the first time [O-O bond length: 1.492(2) Å].
Gesehen am 15.12.2022